Evaluation of treated water produced by the Arkabalo water treatment plant of the Metro Roxas water district , Roxas city - Beba , Maria Alicia Maganto
Quality of the treated water produced by the Arkabalo Water Treatment Plant of the Metro Roxas Water District (MRWD), Roxas City was evaluated.